Synthesis of some surfactant-type acid dyes and their low-temperature dyeing properties on wool fiber. (1st May 2019) - Sun, Jie; Wang, Haiying; Zheng, Chunling; Wang, Guowei
Abstract: Dyeing wool fiber consumes considerable energy and causes contamination, and low-temperature dyeing of wool fiber is a long-standing and often-mentioned topic. The modification of wool fibers and the introduction of novel dyeing processes are common approaches to resolve these issues. In this paper, we attempt to solve these problems from the aspect of dyes. Select tadpole-shaped and surfactant-type acid dyes (D1-D4), which contain a long-chain alkane tail, an anionic chromophore head (azo H acid or amine-substituted bromamine acid) and a polyether segment in their structures, were synthesized, and their low-temperature (15–20 °C below boiling) dyeing properties were investigated. The results indicated that D1-D4 possessed surface activity and could reduce the surface tension of water at low concentrations. These surfactant-type compounds were milling acid dyes with an optimum dyeing pH of 5–6. In comparison with Acid Red 35 and Acid Blue 25, dyes D1-D4 performed certain low-temperature dyeing properties and promoted the exhaustion rate, especially during dyeing at temperatures below 80 °C. The adsorption mechanisms of D1-D4 were analyzed, and the substantivity, leveling and fastness properties of D1-D4 were also tested. Dyes D1-D4 were found to have good substantivity compared with AR35 and AB25, and their leveling properties and color fastness were good. The results indicate that with improvements in dye structures, low temperature dyeing of wool fiber is feasible. Graphical abstract: Image 100